LncRNA MAGI2-AS3 Inhibits Prostate Cancer Progression by Targeting the miR-142-3p - Hu, Renbao; Wu, Pei; Liu, Jianhui (Hormone and Metabolic Research, 2022)
Prostate cancer is a common male cancer with high morbidity and mortality worldwide. According to current research, the integration of long non-coding RNA (lncRNAs) and microRNA(miRNAs) can be expressed in a variety of cancers and play an important role in diagnosis. Based on this, this study explored the clinical role of lncRNA MAGI2-AS3 (MAGI2-AS3) in prostate cancer. By detecting the expression levels of MAGI2-AS3 and miR-142-3p, the correlation between the MAGI2-AS3 expression and the characteristics of clinical data was analyzed. ROC curve analysis was performed and the area under the ROC curve (AUC) was used to evaluate the diagnostic value of MAGI2-AS3 in distinguishing prostate cancer patients from healthy controls. The function of MAGI2-AS3 in prostate cancer cells was explored through CCK-8 and Transwell assays, and the relationship between MAGI2-AS3 and miR-142-3p was investigated by luciferase activity assay. MAGI2-AS3 has descended expression while miR-142-3p has an ascendant one in prostate cancer serum samples and cells. ROC curve analysis revealed that the AUC was 0.953 for MAGI2-AS3, with a sensitivity of 91.5% and specificity of 84.7%. Overexpression of MAGI2-AS3 in LNCaP and PC3 cells suppressed the biological function of the cell including proliferation capacity, migration level, and invasion. MAGI2-AS3 was considered a diagnostic biomarker for prostate cancer patients and inhibited prostate cancer progression by targeting miR-142-3p.
Keywords: lncRNA MAGI2-AS3; miR-142-3p; prostate cancer; diagnostic; migration; invasion